(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2025)
The study examined the perception and readiness of online teaching among lecturers of Colleges of education in Jigawa State. The study was carried out with four objectives, which are to; find out lecturers’ perception on online teaching in Colleges of Education in Jigawa State; identify lecturers’ readiness for the use of internet in teaching in Colleges of Education Jigawa State; find out the; determine the extent of interaction between lecturers’ perception and readiness in the use of mobile phones ,computers, tablets and software applications on the use of online teaching in Colleges of Education in Jigawa State; and assess the extent of lecturers’ utilisation of online teaching in Colleges of Education in Jigawa State. Four research questions and four hypotheses were formulated in line with the above-mentioned objectives. The study employed descriptive survey design with a total population of four hundred and thirty-two (432) and a sample size of three hundred and sixty-four (365) which was arrived at using researcher advisor table. The Data for the study was collected using questionnaire developed by the researcher titled Lecturers’ Perception and Readiness of Online Teaching Question (LPRAOTQ). The data collected were analyzed statistically using Statistical Package for Social Sciences (SPSS) version 25, at both descriptive and inferential levels. At descriptive level, the research questions were answered using mean and standard deviation. At inferential level, the hypotheses were tested using Chi-square and Kruskal-Wallis (H) tests. The findings of the study revealed a significant difference between lecturers’ perceptions of online teaching and the actual practice of online teaching. This suggests that lecturers may harbor misconceptions about the practical aspects of online teaching. The study also found that there was no significant difference in the preparedness of lecturers on the use of Internet for teaching in colleges of education in Jigawa State. This finding suggests that lecturers view online pedagogical approaches favourably and do not perceive strong barriers to their adoption. Another finding from the study is that there was no significant difference in lecturers’ perception and readiness in the use of ICT tools for online teaching in colleges of Education in Jigawa State, among other findings. Based on the findings of the study, it was concluded that there was a significant difference between lecturers’ perceptions of online teaching and the actual practice of online teaching and It was recommended among others that teacher educators should positively perceived online learning as effective leaning method for teacher education; teachers, school managers and National Commission for Colleges of Education (NCCE) should promote the use of ICT and internet in teacher education institutions; and college management and other relevant stakeholders should provide ICT and internet facilities in the Colleges of Education in Jigawa State.